(untitled) (Homiletic, 2011)
Much has been written concerning the New England Puritan Jonathan Edwards, addressing his multifaceted activities as a theologian, preacher, revivalist, pastor, polemicist and missionary. In particular this study focuses upon the rhetorical influences that shaped his preaching ministry: his personal faith experiences, the preaching of his father and grandfather, the Puritan preaching tradition, and the rhetoric of Peter Ramus. While he preached within the sometimes narrow constraints of his New England Puritan tradition, Edwards nonetheless found some freedom to experiment with the classic inherited Puritan tripartite sermon form. Although he never truly departed from this sermon format, his attempts at innovation within his tradition serves as a model for preachers today. Such a legacy may well inspire preachers operating within the confines of hermeneutical or denominational tradition, but who seek to reconfigure elements of their inherited preaching influences.